Technology Architecture and System Design Patterns of Immersive E-Learning in Building Engineering Education: A Systematic Literature Review - Mubarroq, Ahmad Yudi; Muhammad Aris Ichwanto; Luhur Adi Prasetya; Dea Nisfuha Anindya; Tee Tze Kiong (Journal of Information Technology and Computer Science, 2026)
The digital transformation of Industry 4.0 necessitates a fundamental restructuring of Architecture, Engineering, and Construction (AEC) pedagogy through high-fidelity immersive environments. However, current systems often prioritize isolated interaction over the underlying technology architectures required for long-term effectiveness. This research conducted a systematic review of 100 peer-reviewed articles (2018–2025) using the PRISMA 2020 framework and CASP quality appraisal instrument to map functional system configurations. Results indicate a significant paradigm shift toward integrated computational ecosystems, where adaptive intelligent units (30%) and sustainability-oriented processing layers (20%) function as core architectural components. These layers enable dynamic cognitive regulation and real-time environmental metric integration, such as Life Cycle Analysis (LCA), directly within virtual design workflows. Furthermore, findings demonstrate that scalability barriers in vocational settings are increasingly mitigated through cloud-native architectures and IFC-based interoperability. This study concludes that the future of immersive e-learning depends on “Sustainability-by-Design” and scalable architectures, providing a strategic blueprint for intelligent, institution-wide digital infrastructures in engineering education..